A Signature-Based Classification of Gastric Cancer That Stratifies Tumor Immunity and Predicts Responses to PD-1 Inhibitors - Li, Song; Gao, Jing; Xu, Qian; Zhang, Xue; Huang, Miao; Dai, Xin; Huang, Kai; Liu, Lian (Frontiers in Immunology, 2021)
Gastric cancer is a leading cause of cancer-related deaths with considerable heterogeneity among patients. Appropriate classifications are essential for prognosis prediction and individualized treatment. Although immunotherapy showed potential efficacy in a portion of patients with gastric cancer, few studies have tried to classify gastric cancer specifically based on immune signatures. In this study, we established a 3-subtype cluster with low (CLIM), medium (CMIM), and high (CHIM) enrichment of immune signatures based on immunogenomic profiling. We validated the classification in multiple independent datasets. The CHIM subtype exhibited a relatively better prognosis and showed features of “hot tumors”, including low tumor purity, high stromal components, overexpression of immune checkpoint molecules, and enriched tumor-infiltrated immune cells (activated T cells and macrophages). In addition, CHIM tumors were also characterized by frequent ARID1A mutation, rare TP53 mutation, hypermethylation status, and altered protein expression (HER2, β-catenin, Cyclin E1, PREX1, LCK, PD-L1, Transglutaminase, and cleaved Caspase 7). By Gene Set Variation Analysis, “TGFβ signaling pathway” and “GAP junction” were enriched in CLIM tumors and inversely correlated with CD8+ and CD4+ T cell infiltration. Of note, the CHIM patients showed a higher response rate to immunotherapy (44.4% vs. 14.8%) and a more prolonged progression-free survival (4.8 vs. 2.7 months) than non-CHIM patients in a microsatellite-independent manner. In conclusion, the new immune signature-based subtypes have potential therapeutic and prognostic implications for gastric cancer management, especially immunotherapy.